Chusquea parviligulata (Poaceae: Bambusoideae: Bambuseae): a new species of C. subg. Chusquea endemic to the Atlantic rainforest of Bahia, Brazil - Andrade, Ray S.; Pianissola, Evandro M.; Vidal, Kaio Vinicius De A.; Mota, Aline Costa Da; Clark, Lynn G.; Oliveira, Reyjane P. (Phytotaxa, 2019)
Chusquea parviligulata, a new species of Neotropical woody bamboo (Bambuseae: Chusqueinae), is herein described and illustrated, and information on its morphology, conservation status and distribution are provided. It is classified within C. subg. Chusquea based on its relatively elongated internodes, differentiated culm leaves, a triangular and vertically oriented central bud, and infravaginal branching. Based on its occurrence in Brazil and the presence of a white waxy band below the nodes and infravaginal branching, C. parviligulata is further assigned to the C. meyeriana informal group. Within this group, C. parviligulata is most similar to C. clemirae and C. longispiculata, sharing the usually evident division of the subsidiary buds/branches into two groups as well as a triangular central bud and little to no fusion of the overlapping margin of the culm leaf sheaths. Chusquea parviligulata is characterized by having 20–42 subsidiary buds per node; foliage leaf blades adaxially scabrous near the margins and otherwise glabrous or sparsely setose and abaxially mostly glabrous, with a tuft of trichomes at the base; foliage leaf blade base attenuate and slightly asymmetric; and an inner ligule 0.05–0.2 mm long, among the shortest recorded for the genus. Chusquea parviligulata is found exclusively in the Serra da Pedra Lascada, a montane Atlantic Rainforest area in southern Bahia, and it has a restricted occurrence within the Serra. We also report a new locality for C. clemirae and confirm that is has infravaginal branching, not extravaginal branching as originally reported.